Pour une archéologie de la critique de paysage - Hervé Brunon (Projets de Paysage)
The notion of landscape criticism constitutes a central concept in the theory developed by the philosopher Rosario Assunto in Il paesaggio e l’estetica (1973). After highlighting the main contributions of the theory, the article draws several research proposals in order to develop a history of the practices in landscape criticism according to a perspective respecting the methodological indications of Michel Foucault on « archeological description». From the Renaissance until now, three main tactical schemes are identified in the discourses expressing a judgment on landscapes : demonstrative, affective and estimated. This heuristic model could apply, for example, to the evolution of the geographical discourses. Lastly, it seems legitimate to question also the project as critical form relating to action, and not only to discourse.